Neutrophilic dermatosis of the dorsal hands associated with hypopharyngeal carcinoma - Cravo, M (2008)
Neutrophilic dermatosis of the dorsal hands (NDDH) is a rare and recently described disorder regarded as a subset of neutrophilic dermatosis, similar to superficial pyoderma gangrenosum and pustular vasculitis. Many currently consider it to be a localized variant of Sweet Syndrome. We describe the case of a 63-year-old male patient with NDDH associated with hypopharyngeal carcinoma. A biopsy demonstrated changes consistent with those seen in Sweet Syndrome, with leukocytoclasia but no signs of true vasculitis. Treatment with oral prednisolone resulted in complete resolution of the lesions in 1 month, with no recurrences. The clinical presentation, the histological features, and the excellent response to oral corticosteroid therapy allowed us to classify this case as NDDH. We emphasize the rare association of this entity with a solid tumor.